Tracing the Consumptive Behavior of Students in Online Gambling: Between Digital Lifestyle and Welfare Challenges - Affan, Moh (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research focuses on analyzing the consumptive behavior of students involved in online gambling, specifically, the factors that affect their involvement, such as social pressure, uncertain expectations of winning, and materialistic lifestyle needs. This type of research is qualitative with a phenomenological approach that seeks to understand students' subjective experiences. The data collection technique used in-depth interviews and direct observation at the two research locations, with a total of 15 participants who had involvement in online gambling activities. The data was analyzed using the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing to identify thematic patterns that reflect gambling-related consumptive behavior. The results of the study show that student involvement in online gambling is triggered by social factors, such as peer encouragement, winning narratives, and pressure to follow a particular lifestyle. Additionally, college students who engage in online gambling show a reliance on uncertain winnings, leading to a deepening cycle of financial losses and negative psychological impacts, including anxiety and decreased academic motivation. The implications of this study emphasize the need for interventions in the form of education on financial management and financial literacy, as well as psychosocial support to reduce the impact of students' consumptive behavior in online gambling. In addition, this research is expected to encourage educational institutions to pay attention to the role of the social environment in influencing students' behavioral choices and develop effective prevention programs.